Dosed Walking: Under Sign of Health Improving and Rehabilitation - T. N. Malyarenko; G. V. Chudinov; A. A. Kornienko; Yu. E. Malyarenko (Медицинский вестник Юга России, 2011)
Here is shown on the base of the foreign literature review that walking could cause not only positive, but also negative effects. The last one are the result of discrepancy of walking parameters to person’s trained level in the case of inobservance of individualization principle. In this connection in article the methodology of drawing up of medical-improving programs of the dosed walking and efficiency of their use is discussed.